2005
DOI: 10.1115/1.1860562
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Shaped Hole Turbine Film-Cooling Technology

Abstract: Film cooling represents one of the few game-changing technologies that has allowed the achievement of today’s high firing temperature, high-efficiency gas turbine engines. Over the last 30 years, only one major advancement has been realized in this technology, that being the incorporation of exit shaping to the film holes to result in lower momentum coolant injection jets with greater surface coverage. This review examines the origins of shaped film cooling and summarizes the extant literature knowledge concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
191
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 712 publications
(193 citation statements)
references
References 40 publications
1
191
0
1
Order By: Relevance
“…11 in Paper I). Injecting coolant through this row in the presence of showerhead cooling will disturb the state of a fresh boundary layer development with high kinetic energy content due to the showerhead and consequently it will enhance the HTC to a greater extent, which is consistent with the explanation given by Bunker [61]. In this case, both cooling hole types react in the same way to the state of approaching flow.…”
Section: Illustrated Insupporting
confidence: 78%
See 2 more Smart Citations
“…11 in Paper I). Injecting coolant through this row in the presence of showerhead cooling will disturb the state of a fresh boundary layer development with high kinetic energy content due to the showerhead and consequently it will enhance the HTC to a greater extent, which is consistent with the explanation given by Bunker [61]. In this case, both cooling hole types react in the same way to the state of approaching flow.…”
Section: Illustrated Insupporting
confidence: 78%
“…Note that injection through a showerhead will make a thicker boundary layer while at the same time it will enhance the HTC. This figure thus suggests that fan-shaped holes may reduce the kinetic energy within a thick and well-developed turbulent boundary layer and hence reduce the HTC, see Bunker [61], while cylindrical holes will elevate the turbulence level further and enhance the HTC under the same circumstance. Figure 15 indicates that general findings concerning row #1, such as a higher level of HTC for fan-shaped holes compared to cylindrical holes and also elevated HTC when M is increased, can be extended to row #3.…”
Section: Illustrated Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Bunker [2] in his comprehensive review paper on film cooling from shaped holes has pointed out that no single shaping of film hole stands as an optimal geometry for all applications. He also concluded that hole shape maintains the cooling jets closer to surface, enhances film coverage and reduces mixing.…”
Section: Introductionmentioning
confidence: 99%
“…From measurements on a range of the L/D ratio of 1.75 to 18, Lutum and Johnson [5] reported that film-cooling effectiveness generally decreased with decreasing L/D when the ratio was less than 5.0 but showed no significant change for L/D that exceeded 5.0. Bunker [6] examined the origins of the shaped film-cooling hole and summarized the extensive literature regarding the performance of such film holes. In order to evaluate the performance and characteristics of various holeshapes, many numerical studies have been conducted, e.g., Bohn and Moritz [7], Hyams and Leylek [8], Azzi and Jubran [9], Leedom and Acharya [10] and Mahmood et al [11].…”
Section: Introductionmentioning
confidence: 99%